ПАЛЎАНЛАР ҲАҚҚЫНДАҒЫ ӘПСАНА ҲӘМ ГҮРРИҢЛЕР ТИЙКАРЫНДА ОҚЫЎШЫ ЖАСЛАРДЫ БАТЫРЛЫҚҚА, МӘРТЛИККЕ ТАЯРЛАЎДЫҢ ПЕДАГОГИКАЛЫҚ ӘҲМИЙЕТИ - Нурекеев, Б.Т. (ILIM hám JÁMIYET, 2020)
The article deals with the issues of pedagogical significance of folklore and works of fiction devoted to the life and activity of the well-known Karakalpak fighters (palvans) who went in for such kind of sport as wrestling. Eposes, legends, parables and stories about fighters are of a great importance as national value and heritage of the people that are inherited from generation to generation. They play a great role in education of the best human qualities – courage, love and devotion to Motherland, patriotism, in education of comprehensively developed, freely thinking personality, in spiritual-moral and physical development of young generation of our country.